Obligaciones tributarias en la Empresa Bemed Health Care Bmhc S.A., período 2022 y 2023. - Zambrano Zumba, Rigoberto Antonio (2024)
The present research work was carried out in Bemed Health Care Bmhc S.A., a private company dedicated to the wholesale and retail trade of medical supplies and cosmetics (beauty products) in Guayaquil, Guayas province. Taking into account the tax compliance of the SRI, an adequate tax planning should be suggested as an ideal way to avoid legal problems with tax obligations. The problem that will be the object of the research, the justification to know the importance of the case study and the objectives that are expected to be fulfilled once it is solved, are presented and described. The conceptual framework or theoretical framework of the same was elaborated, which allowed the theoretical basis of the whole research; therefore, the methodology of mixed qualitative and quantitative approach was applied; likewise, a bibliographic, inductive, descriptive, field and exploratory design was used. For the preparation of this document, an interview was conducted with the person in charge of the accounting area of the company Bemed Health Care BMHC S.A. where the tax information mentioned in the first specific objective was obtained and represented graphically with its respective analysis and interpretation. The results were elaborated together with the discussion of results that go hand in hand with the specific objectives raised; to conclude; in turn, the conclusions and recommendations of the company for the years 2022-2023 were finalized.